Survei Kecemasan Pemain Sepakbola Universitas PGRI Palembang dalam Menghadapi Pertandingan - M. Taheri Akhbar; Agung Mahendra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
The purpose of this study was to determine how much anxiety the football players from PGRI Palembang University had. The research method used is descriptive quantitative method. Data collection techniques using a questionnaire/questionnaire. The data obtained were analyzed using the percentage formula. The results showed that the anxiety of football players at PGRI Palembang University was based on 2 factors, namely intrinsic factors and extrinsic factors. Intrinsic factors of 77.61% players do not experience anxiety and 22.38% players experience anxiety. Extrinsic factor is 78.25% of players do not experience anxiety and 21.74% of players experience anxiety. In conclusion, the anxiety of football players at PGRI Palembang University in facing matches is in the low category. Keywords: Anxiety, Football Player, Match